G191 Catcam: a new solution for congenital cataract screening?. (12th March 2018) - Duret, A; Humphries, RS; Ramanujam, S; Reid, C; Allen, L
Abstract : Aims: Congenital cataract is the leading cause of childhood blindness worldwide; surgery before 9–10 weeks of age is necessary to optimise visual outcome. We investigated the accuracy of the Newborn Infant Physical Examination (NIPE) red reflex test in the detection of cataracts and compared it to CatCam, a novel hand-held infrared digital imaging device. Methods: We first reviewed the notes of all children having cataract surgery under 3 years of age over a 2 year period to determine how and when referral had occurred. Subsequently, we undertook proof-of–concept testing for CatCam in two populations: one of normal neonates undergoing NIPE screening, and secondly in an enriched population of children attending a tertiary paediatric ophthalmology clinic. Evaluation of ease of use and statistical comparison of diagnostic accuracy was made between CatCam and red reflex testing by direct ophthalmoscope (DO). Results: 33 children (45 eyes) underwent cataract surgery during the 2 year study period. Only 10 were referred following abnormal NIPE and fewer than 50% were referred before 9 weeks of age. Of the 90 normal newborns examined at the first NIPE check, visually insignificant congenital media opacities were detected in 9 (10%) infants on CatCam imaging alone. CatCam examination was subjectively easier than red reflex testing, particularly in non-Caucasian infants. Finally, 111 subjects attending a specialist clinic were examined with DO and CatCam prior to pupil dilatation and specialist review. The sensitivity and specificity for media opacity was 100% for CatCam and 71% and 62% respectively for the DO (p=0.01). Conclusion: Although some cataracts may have developed postnatally, our audit suggests that the sensitivity of the NIPE examination is poor and that many infants with cataracts are diagnosed late. The clinical studies demonstrate the advantages of CatCam over DO examination, particularly its high sensitivity and specificity due to the absence of pupil constriction, better reflectivity of infrared light from non-Caucasian fundi and ability to document the images facilitating a second opinion.